Enhancer-driven cell type comparison reveals similarities between the mammalian and bird pallium - Hecker, Nikolai; Kempynck, Niklas; Mauduit, David; Abaffyová, Darina; Vandepoel, Roel; Dieltiens, Sam; Borm, Lars; Sarropoulos, Ioannis; González-Blas, Carmen Bravo; De Man, Julie; Davie, Kristofer; Leysen, Elke; et al. (Science, 2025)
Combinations of transcription factors govern the identity of cell types, which is reflected by genomic enhancer codes. We used deep learning to characterize these enhancer codes and devised three metrics to compare cell types in the telencephalon across amniotes. To this end, we generated single-cell multiome and spatially resolved transcriptomics data of the chicken telencephalon. Enhancer codes of orthologous nonneuronal and γ-aminobutyric acid-mediated (GABAergic) cell types show a high degree of similarity across amniotes, whereas excitatory neurons of the mammalian neocortex and avian pallium exhibit varying degrees of similarity. Enhancer codes of avian mesopallial neurons are most similar to those of mammalian deep-layer neurons. With this study, we present generally applicable deep learning approaches to characterize and compare cell types on the basis of genomic regulatory sequences.
Gesehen am 01.12.2025